Case Report: Direct Access Genetic Testing and A False‐Positive Result For Long QT Syndrome. Issue 1 (30th August 2015) - Predham, Sarah; Hamilton, Sara; Elliott, Alison M.; T. Gibson, William
Abstract: We report the case of a woman who pursued direct access genetic testing and then presented with concerns regarding a positive test result for Long‐QT syndrome. Although the result ultimately proved to be a false positive, this case illustrates that costs associated with follow‐up of direct access genetic testing results can be non‐trivial for both the patient and for health care systems. Here we raise policy questions regarding the appropriate distribution of these costs. We also discuss the possibility that, when confronted by a direct access genetic test result that reports high risk for one or more actionable diseases, a family physician might feel compelled to act out of a desire to avoid liability, even when information regarding the accuracy and validity of the testing were not easily accessible. This case outlines lessons that can easily be translated into clinical practice, not only by genetic counselors, but also by family physicians, medical specialists and members of the public.